2016
DOI: 10.1007/s12205-016-0856-z
|View full text |Cite
|
Sign up to set email alerts
|

Back-fill grout experimental test for discharged soils reuse of the large-diameter size slurry shield tunnel

Abstract: The construction of a slurry shield tunnel produces large amount of excavated soil. Direct discharge of the excavated soil by transportation not only increases the overall construction cost but also raises environmental concerns of pollution. In this study, we explore in-situ recycle of excavated soil in the Nanjing Yangtze River tunnel project as the back-fill grout. A series of laboratory were carried out to determine the synchronous grout parameters, including compression strength and shear strength, initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 15 publications
(13 reference statements)
2
16
0
Order By: Relevance
“…Shinde et al [29] reused marble dust and granite dust in injection grouts, which reduced the cost of grout by 70% to 75% less than market cost. Zhou et al [30] confirmed the feasibility of discharged sandy soil from a slurry shield tunnel as a material of back-fill grout. Çınar et al [31] investigated the effect of waste marble powder on the fluidity of cement based grout mixtures and found 15% was the upper limit of reutilization.…”
Section: Introductionmentioning
confidence: 93%
“…Shinde et al [29] reused marble dust and granite dust in injection grouts, which reduced the cost of grout by 70% to 75% less than market cost. Zhou et al [30] confirmed the feasibility of discharged sandy soil from a slurry shield tunnel as a material of back-fill grout. Çınar et al [31] investigated the effect of waste marble powder on the fluidity of cement based grout mixtures and found 15% was the upper limit of reutilization.…”
Section: Introductionmentioning
confidence: 93%
“…e measured earth pressure fluctuated a week after tail passing. e measured total earth pressure acting on the crown level and [6]. w � water content, c � natural unit weight of the soil, e � void ratio, E s � compression modulus of the soil, C � cohesion, φ � angle of internal friction, f � bearing capacity of the ground, C u � the uniformity coefficient, and C c � the curvature coefficient.…”
Section: 1mentioning
confidence: 99%
“…Multiple factors influencing the earth pressure around the tunnel lining, including the engineering geology, the depth of the overburden, the ground water level, the excavation method, interactions between the lining and soil and the construction behaviour, operational parameters, and grouting parameters, have been indicated by many scholars [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al [ 19 ] studied the reuse of fine sand discharged from shield excavation for grouting behind the lining. Zhou et al [ 20 ] explored in-situ recycle of excavated sandy soil in the Nanjing Yangtze River tunnel project as the back-fill grout instead of purchased sand. Zhang et al [ 21 ] used waste mud of slurry shield and fine sand as synchronous grouting materials.…”
Section: Introductionmentioning
confidence: 99%